A study on the determinants of capital structure of food and beverages companies in Malaysia / Amni Hawana Helmy and Aqilah Hairudin - Helmy, Amni Hawana; Hairudin, Aqilah (Faculty of Business and Management, 2019)
The objective of the study is to investigate the determinants of capital structure of food and beverages companies in Malaysia. The investigation is focus on the firm-specific factors such as liquidity (CR), tangibility (PPETA), firm’s growth (GTA), profitability (ROA) and size of firm (TA) that influence the capital structure decisions of food and beverages companies. The debt to equity ratio is used as a proxy to measure the capital structure of the company. The analysis of this study performed by using the panel data model; random effects model for 15 companies listed in Bursa Malaysia Berhad under food and beverages sector in Malaysia during the periods of 2010 to 2017. The results of this study indicate the determinants that have positive impact on capital structure are firm’s growth, profitability and size of firm. In contrast, the determinants that give negative impact on the capital structure are liquidity and tangibility. The value of R-square is 0.673589 which indicates that 67.36 percent of capital structure variation can be explained by all the variation of independent variables that include in this study which are liquidity, tangibility, firm’s growth, profitability and size of firm while the remaining of 32.64 percent explained by other factors that are omitted in the model.